WANTED: MORE COST ACCOUNTING FOR GOVERNMENT. - Mikesell, R. M. (The Accounting Review, 1947)
Abstract In this article the author discusses notable strides in the field of accounting for public funds during the past fifteen years, as of July 1947. A logical inference is that a large measure of this improvement is an outgrowth of the taxpayers' genuine concern over the expenditure of vast sums of public funds and a widespread belief that substantial retrenchments on a voluntary basis may not be expected from the offices and agencies concerned, in some quarters expansion continues to be the order of the day. Recent budget requests of many state and local governments in the U.S. have assumed proportions of surprising magnitude, resulting largely, it must be admitted, from withdrawals of financial aid by the U.S. government and from insistent public demands for more or better service, and from public-employee demands for standards of remuneration comparable to those enjoyed by persons in non-governmental employment. The law-making body of one midwestern state, sitting in the first quarter of 1947, found itself figuratively engulfed in a flood of bills calling for more public money, the requests covering practically the whole range of governmental activity from the township justice of the peace on one hand to departments and agencies of the state on the other.